ASAS PACTA SUNT SERVANDA DIKAITKAN DENGAN PENYELENGGARAAN JASA PENDIDIKAN ASING DI INDONESIA OLEH MONASH UNIVERSITY (Lex Jurnalica, 2018)
AbstractThis research aims to provide clarity regarding the regulation and implementation of educational services liberalization under GATS in the analysis of the National Education Law as well as the suitability of the organization of foreign education by Monash University in Indonesia with Law national Education System Number 20 of 2003. This research was conducted by legal normative approach and examinedusing field study to get the primary data and literaly study to get the secondary data. Then all data collected were analyzed with qualitative methods. Based on the research, the result showed that the setting and implementation of liberalization of higher education services in Indonesia by 1995 GATS in education services in the analysis of the National Education System Law Number 20 of 2003 is the Education Law to support the liberalization of education services in Indonesia. This can be seen from Article 65 of the Education Law which regulates the implementation of other state educational institutions that provide education by representatives of foreign countries and the implementation by the foreign educational institution accredited in the country. Liberalization of education services in Indonesia through the organization of foreign education by Monash University does not comply with the framework of the Law on National Education System Number 20 of 2003.Â Keywords: foreign universities, commercial presence, foreign education serviceÂ AbstrakMetode pendekatan yang digunakan dalam penelitian ini bersifat yuridis normative dengan metode diskriptif analitis. Penelitian ini dikaji dengan menggunakan studi lapangan untuk memperoleh data primer dan studi kepustakaan untuk memperoleh data primer dan studi kepustakaan untuk memperoleh data sekunder. Kemudian seluruh data yang terhimpun dianalisis dengan menggunakan metode kualitatif. Hasil penelitian menunjukkan bahwa pengaturan dan penerapan liberalisasi jasa pendidikan dalam analisis Undang-Undang Sistem Pendidikan Nasional Nomor 20 Tahun 2003 ialah UU Sisdiknas mendukung liberalisasi jasa pendidikan di Indonesia. Hal ini dapat diketahui dari Pasal 65 UU Sisdiknas yang mengatur mengenai penyelenggaraan pendidikan oleh lembaga Negara lain yaitu penyelenggaraan pendidikan oleh perwakilan Negara asing dan penyelenggaraan oleh lembaga pendidikan asing yang terakreditasi di negaranya. Liberalisasi jasa pendidikan di Indonesia melalui penyelenggaraan pendidikan oleh Monash University tidak sesuai dengan kerangkaUndang-Undang Sistem Pendidikan Nasional Nomor 20 tahun 2003 karena Monash University dalam praktik penyelenggaraan pendidikan asing di Indonesia tidak mendapat izin dari Kemendiknas, tidak terakreditasi di BAN-PT dan tidak berbentuk yayasan yang bersifat sosial.Â Kata kunci : universitas asing, kehadiran komersial, jasa pendidikan asing